2020
DOI: 10.1038/s41598-020-63885-w
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of mycorrhizal Tulasnella associated with epiphytic and rupicolous orchids from the Brazilian Atlantic Forest, including four new species

Abstract: the genus Tulasnella often forms mycorrhizas with orchids and has worldwide distribution. Species of this genus are associated with a wide range of orchids, including endangered hosts. initially, species identification relied mostly on morphological features and few cultures were preserved for later phylogenetic comparisons. In this study, a total of 50 Tulasnella isolates were collected from their natural sites in Minas Gerais, Brazil, cultured, and subjected to a phylogenetic analysis based on alignments of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 52 publications
(79 reference statements)
1
14
0
Order By: Relevance
“…Among them, the dominant genera were Epulorhiza, Fusarium , and Tulasnella. Tulasnella and Epulorhiza were considered universal orchid symbionts, 26 i.e., they can form mycorrhizal fungi with most orchids. 27–37 Studies have reported that Fusarium is the dominant species of P. armeniacum, P. micranthum , and Bletilla striata .…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the dominant genera were Epulorhiza, Fusarium , and Tulasnella. Tulasnella and Epulorhiza were considered universal orchid symbionts, 26 i.e., they can form mycorrhizal fungi with most orchids. 27–37 Studies have reported that Fusarium is the dominant species of P. armeniacum, P. micranthum , and Bletilla striata .…”
Section: Discussionmentioning
confidence: 99%
“…The OTU TU11 (Tulasnellaceae) was the most frequently detected OTU in Dendrobium okinawense roots and was subjected to phylogenetic analysis using ITS sequences. To confirm the taxonomic placement of TU11 and its relationship to other known Tulasnella species, reference sequences of Tulasnella species from Freitas et al (2020), as well as all representative sequences from GenBank with >97% homology with TU11, were also included in the analysis. Sequences of Tulasnellaceae taxa obtained from Dendrobium species in previous studies (see Table S2) were included in the analysis as well.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…Orchidaceae, one of the biggest flowering plant families, is widely distributed in almost all parts of the world. However, many orchid species are listed as endangered owing to habitat degradation and dependence on other organisms, i.e., pollinators (Suetsugu et al 2015;Freitas et al 2020). Moreover, establishing orchids in the natural habitat is always complicated, even in suitable conditions (Pujasatria et al 2020).…”
Section: Introductionmentioning
confidence: 99%